2022
DOI: 10.2460/javma.20.09.0488
|View full text |Cite
|
Sign up to set email alerts
|

Dogs undergoing surgical excision of mast cell tumors are not at increased risk of incisional complications

Abstract: OBJECTIVE To retrospectively compare the incidence of incisional complications in dogs undergoing surgery for mast cell tumors (MCTs) and soft tissue sarcomas (STSs). ANIMALS 218 dogs. PROCEDURES Dogs that underwent excision of ≥ 1 MCT, STS, or both from January 2014 to July 2019 and had ≥ 30 days postoperative follow-up were included. Signalment; anesthesia and surgery time; administration of propofol; tumor type, grade, location, and size; intended surgical margins; histologic margins; perioperative radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…The concerns regarding glucocorticoid treatment for cytoreduction include whether surgical margins based on post-treatment tumor size would yield complete histologic margins and whether treatment would be associated with an increased risk of post-operative incisional complications. In our study and others, surgical margins based on tumor size following pre-operative treatment with glucocorticoids have yielded complete histologic margins [22,40,99]. A long-term prospective evaluation of these patients is warranted to determine whether the local tumor recurrence rate is impacted [54].…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…The concerns regarding glucocorticoid treatment for cytoreduction include whether surgical margins based on post-treatment tumor size would yield complete histologic margins and whether treatment would be associated with an increased risk of post-operative incisional complications. In our study and others, surgical margins based on tumor size following pre-operative treatment with glucocorticoids have yielded complete histologic margins [22,40,99]. A long-term prospective evaluation of these patients is warranted to determine whether the local tumor recurrence rate is impacted [54].…”
Section: Discussionmentioning
confidence: 63%
“…A long-term prospective evaluation of these patients is warranted to determine whether the local tumor recurrence rate is impacted [54]. Post-operative complications following MCT resection, whether wide or intentionally marginal, are reported to be 13-29% [41,99]. Although not evaluated in our study, others have reported that dogs treated with pre-operative glucocorticoids have not had an increased risk of post-operative complications [22,40,99].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The database searches retrieved more than 800 results that were narrowed down to 22 meeting eligibility criteria ( 7 12 , 17 , 18 , 34 , 35 , 45 – 56 ). A pooled population of 3,745 patients was analysed and, where reported, the median number of MCTs at presentation was 2 (range 2–6).…”
Section: Resultsmentioning
confidence: 99%
“…for 8 days) and a H 2 (famotidine: 0.25–0.5 mg/kg b.i.d. for 8 days) histamine receptor blocker both to be started on treatment day, were dispensed, and a suitable pre-emptive analgesia plan formulated subsequent to enrolment ( 2 , 35 ).…”
Section: Methodsmentioning
confidence: 99%